2014
DOI: 10.2478/intag-2014-0044
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous monitoring of electrical capacitance and water uptake activity of plant root system

Abstract: A b s t r a c t. Pot experiments were designed to test the applicability of root electrical capacitance measurement for in situ monitoring of root water uptake activity by growing cucumber and bean cultivars in a growth chamber. Half of the plants were inoculated with Funneliformis mosseae arbuscular mycorrhizal fungi, while the other half served as non-infected controls. Root electrical capacitance and daily transpiration were monitored during the whole plant ontogeny. Phenology-dependent changes of daily tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Investigations of root development with time using ECM showed that there are important temporal variations in the measured capacitance (Cseresnyés et al., 2018; Cseresnyés, Rajkai, & Takács, 2016; Cseresnyés, Takács, Füzy, & Rajkai, 2014; Cseresnyés, Takács, Füzy, Végh, & Lehoczky, 2016; Dalton, 1995). Cseresnyés et al.…”
Section: Methods Targeting Electrical Resistivitymentioning
confidence: 99%
See 2 more Smart Citations
“…Investigations of root development with time using ECM showed that there are important temporal variations in the measured capacitance (Cseresnyés et al., 2018; Cseresnyés, Rajkai, & Takács, 2016; Cseresnyés, Takács, Füzy, & Rajkai, 2014; Cseresnyés, Takács, Füzy, Végh, & Lehoczky, 2016; Dalton, 1995). Cseresnyés et al.…”
Section: Methods Targeting Electrical Resistivitymentioning
confidence: 99%
“…Cseresnyés et al. (2014) found that root water uptake and C root increased from the emergence of a seedling to the beginning of flowering and then decreased continuously during the fruit setting for cucumber ( Cucumis sativus L.) and bean ( Phaseolus vulgaris L.). Similarly, ECM presented in Cseresnyés et al.…”
Section: Methods Targeting Electrical Resistivitymentioning
confidence: 99%
See 1 more Smart Citation
“…These methods, long established in the near-surface geophysics community, capture electrical material properties of the subsurface, or laboratory samples, which can then be related to geophysical properties such as temperature (e.g., Sen and Goode 1992), salinity (e.g., Rhoades et al 1989), porosity/soil water content (e.g., Archie 1942;Oberdörster et al 2010;Whalley et al 2017), clay content (e.g., Breede et al 2012), and even certain root parameters (e.g., Chloupek 1972;Dalton 1995;Cseresnyés et al 2013;Wu et al 2017, and references therein). It has also been recognized that electrical methods can not only be used to characterize structural, but also functional properties of root systems (e.g., Dalton 1995;Cseresnyés et al 2014Cseresnyés et al , 2016.…”
Section: Introductionmentioning
confidence: 99%